2018
DOI: 10.3329/ptcb.v28i1.37205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethrel on Organogenesis of Protocorm-like bodies in Dendrobium kingianum In vitro

Abstract: This study attempted to understand the effects of BAP and ethrel on organogenesis of protocorm-like bodies (PLBs) in Dendrobium kingianum under white fluorescent lamps in vitro. BAP is the most effective cytokinin for multiplication in plant tissue culture. Ethrel regulates many aspects of plant morphogenesis. The highest number of PLBs (13.1) as against in control (8.1) and the highest number of developing shoots (2.1) was recorded in the medium containing 0.1 mg/l BAP combined with 1 mg/l ethrel. Increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…A long-lasting application of blue light enhances the synthesis of ALA and eliminates the unfavorable effect of red light in this respect (Fan et al 2013). The literature data confirm the inhibitory effect of red light on the production of chlorophyll that we also observed in our study (Li et al 2010;Fan et al 2013;Habiba et al 2014;Bello-Bello et al 2016;Coelho et al 2021), and carotenoids (Liu et al 2011;Fan et al 2013;Pawłowska et al 2018b;Coelho et al 2021) in in vitro plant cultures. RBUV light also inhibited the synthesis of photosynthetic pigments, both chlorophylls and carotenoids, in L. candidum cultures.…”
Section: Effect Of Spectral Combination On Photosynthetic Pigment Con...supporting
confidence: 89%
“…A long-lasting application of blue light enhances the synthesis of ALA and eliminates the unfavorable effect of red light in this respect (Fan et al 2013). The literature data confirm the inhibitory effect of red light on the production of chlorophyll that we also observed in our study (Li et al 2010;Fan et al 2013;Habiba et al 2014;Bello-Bello et al 2016;Coelho et al 2021), and carotenoids (Liu et al 2011;Fan et al 2013;Pawłowska et al 2018b;Coelho et al 2021) in in vitro plant cultures. RBUV light also inhibited the synthesis of photosynthetic pigments, both chlorophylls and carotenoids, in L. candidum cultures.…”
Section: Effect Of Spectral Combination On Photosynthetic Pigment Con...supporting
confidence: 89%
“…Conversely, BW-trehalose produced the second largest number of shoots (Table 2). LEDs have been successfully applied in vitro in various plant species [20,[29][30][31][32][33]. The ideal light stipulation for each plant species is unique.…”
Section: Discussionmentioning
confidence: 99%
“…A number of in vitro studies have reported vigorous plant growth under LEDs. LED lights have been previously used for PLB organogenesis in Cymbidium finlaysonianum [29], Dendrobiumkingianum [30,31], hybrid Cymbidium [32,33], and plantlet regeneration in gerbera [34]. A series of studies have already been conducted to improve the tissue culture of Phalaenopsis using a number of factors.…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthetic capacity was highest in Betula pendula Roth [ 154 ] and in chrysanthemum ( Dendranthema grandiflorum ) [ 42 ] when the plantlets were exposed to BL as compared to RL. In Dendrobium kingianum , the average number of PLBs and the chlorophyll content were highest under B-LEDs, in contrast to the explants cultured under R-LEDs where the highest shoot formation and fresh weight were observed [ 99 ]. Likewise, a study of Oncidium PLBs by Mengxi et al [ 90 ] showed that chlorophyll a and b and carotenoid levels and the greatest growth were detected under B-LEDs.…”
Section: Effects Of Spectral Quality Of Light On In Vitro Proliferationmentioning
confidence: 99%